2016
DOI: 10.1002/macp.201600471
|View full text |Cite
|
Sign up to set email alerts
|

Peanut-Like Crystals in Polycarbonate/Plasticizer Blends

Abstract: Bisphenol‐A polycarbonate (BAPC) crystal with unusual morphology is obtained in the solution‐cast films of BAPC/plasticizer blends. It seems like Siamese twin spherulites, and owns a peanut‐like morphology with more than one nucleating sites. Furthermore, concentric black dotted rings, which should be the aggregation regions of plasticizers, are also observed within the peanut‐like crystals. The peanut‐like morphology has no selectivity to the kinds of plasticizer and the casting temperature. The development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to the literature [57] the peak registered on heating at ca. 150 °C is related to melting of l , d -PLA, while around 55 °C to glass-transition [58].…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature [57] the peak registered on heating at ca. 150 °C is related to melting of l , d -PLA, while around 55 °C to glass-transition [58].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of two aromatic rings bridged by methylene unit in PC leads to low chain flexibility. , Although bulk PC is hard to crystallize, dense fibrillar lamellar crystals were observed by AFM in the 30 nm thick spin coated PC films after annealing at 200 °C for 24 h by Ata et al Von Falkai et al reported that the first crystallites of PC appeared after one full day and it took longer than a week to obtain a complete PC spherulite at 190 °C . Along these years, various methods have been tried to obtain high crystallinity for PC samples, such as by blending, adding plasticizers, surfactants, solvent vapor exposure, or ultrasound-assisted crystallization (sonocrystallization), and so on. In order to lower the temperature of crystallization, Sundararajan studied the crystallization of PC in the presence of a surfactant, which required a temperature of 80 °C for 24 h, far less than the others as reported to date, whereas the report of the crystallization of polycarbonate in the presence of a surfactant is limited.…”
Section: Introductionmentioning
confidence: 99%